Line Breaths in Allen Ginsberg’s Poetry - Anna Aublet (Transatlantica)
“I am not thoroughly satisfied with what he has done. I have told him—I mean I am disgusted with him and his long lines.” As Williams delivers this message to his friend Walter Sutton, he condemns what he sees as Allen Ginsberg’s inability to both carve and curb his verse. This article explores what occurs when the line won’t break, when it goes on stubbornly wandering off the page. Ginsberg’s long verse thus comes to index a break in his modernist lineage. It operates a departure from his modernist masters, Williams, Pound and Eliot. According to the Beat poet, the line should not be modelled after the length of the page, but rather attempt to break its delineations so as to return the poem to its original breath. These observations invite us to take a closer look at the long line as both a political and personal expression of the poet’s journey on and off the page.